Revival. A case study in the church of Christ in Thailand. - Coertzen, P; Son, SH (Nederduitse Gereformeerde Teologiese Tydskrif, 2004)
The Thai revival of 1938-1939 resulting from John Sung’s campaigns is the greatest revival movement in Thai church history. Nevertheless, the resultant fruit of John Sung’s ministry was meagre compared to the results of his work in other countries, because the historical, socio-cultural, religious, and political situations of Thailand influenced the results of John Sung’s campaigns. The revival was confined to the Church of Christ in Thailand (CCT) with which the missionaries of the American Presbyterian Mission (APM) were involved. The aim of this article is to explore the phenomena, characteristics, and emphases of the revival movement. An ecclesiological analysis and evaluation will also be considered regarding John Sung’s campaigns.